Downscaled GCM projections of winter and summer mass balance for Central European glaciers (2000–2100) from ensemble simulations with ECHAM5‐MPIOM. (17th May 2012) - Springer, Claudia; Matulla, Christoph; Schöner, Wolfgang; Steinacker, Reinhold; Wagner, Sebastian
Abstract This study is based on the study from Matulla et al. (2009) where the glacier under estimation has been Peyto Glacier in Canada. The same methods have been used for five Austrian glaciers; projections of glacier mass balance are generated from ensembles of general circulation model (GCM) simulations by the use of direct statistical downscaling. Thereby, the general features of the atmospheric circulation over an expanded geographical region covering the European Alps are linked empirically to winter and summer mass balance records measured at five glaciers in Austria. The projections are taken from an ensemble of ECHAM5‐MPIOM simulations forced with the IPCC‐SRES scenarios A1B and B1. Results based on the statistical downscaling indicate decreasing balances for both winter and summer. These results suggest continued frontal recession and downwasting of the alpine glaciers in this region until 2100. For Jamtalferner, these suggestions reach reductions of about 1000 mm water equivalent in summer. Copyright © 2012 Royal Meteorological Society